RETRACTED: Pengaruh metode perebusan terhadap uji fitokimia daun mangrove Excoecaria agallocha - Puspitasari, Dian; Desrita, Desrita (Acta Aquatica: Aquatic Sciences Journal, 2019)
AbstrakFollowing a rigorous and careful concerns and consideration in the review of the article published in JActa Aquatica entitled Pengaruh metode perebusan terhadap uji fitokimia daun mangrove Excoecaria agallocha Vol 6, No 1, pp. 28-31, April 2019, DOI: https://doi.org/10.29103/aa.v6i1.1046This paper has been found to violate the  principles of Acta Aquatica: Aquatic Sciences Journal publication and has been retracted. The article has been drawn by the Author. The document and its content have been removed from Acta Aquatica: Aquatic Sciences Journal, and reasonable effort should be made to remove all references to this article.